Celebrating the American home : 50 great houses from 50 American architects - Bouknight, Joanne Kellar (Newtown, CT : Taunton Press, 2005)
Celebrating the American Home brings together the best 50 houses featured in books from the Taunton Press in the past five years. These houses, which range from the irresistibly cozy to the magisterial to the daringly innovative, were selected by a panel of distinguished residential architects who are members of the American Institute of Architects including Jeremiah Eck, Duo Dickinson, and John Connell, who chose the houses based on how well they reflected the core qualities of great home design. Each house is showcased in four to six pages and shown from a variety of views, with a brief introductory text explaining what makes the house unique and color photographs illustrating the key design features. Sidebars elaborate on why the architects selected each house, while an introductory chapter provides a detailed explanation of those core qualities that distinguished a great home: human-size scale, livability, quality of craft, connection to site, and distinctive design.
What makes a great American home? --
A traditional house with modern compsoure --
Shipshape on Martha's Vineyard --
A timber frame redressed --
A cottage takes root in Maine --
Cool, calm, and composed --
A seaside house bares its bones --
Easy on the earth, easy on the eyes --
A classical perspective on a romantic setting --
Treading lightly on the dunes --
A house of the woods --
Recreating the past at water's edge --
A house in tune --
A comfortable fit on the New England coast --
Give and take revives a Connecticut cape --
A study in contrast --
Two into one --
A new farmhouse takes its place in history --
Courting quiet with geometric harmony --
Catch the breeze, renew the spirit --
In response to the climate --
A serene retreat --
Local color infuses a modern house --
Pueblo and Spanish influences shape a hillside house --
A timeless farmhouse --
Small footprint but tall in stature --
Townhouse tranformation --
A clear field of vision --
New house with an ageless soul --
Cube with a view --
Canadias boathouse --
Wright-inspired ranch --
Riverside, shingle style --
Style and delight on a budget --
A composition in balance, light, and craft --
Rambling farmhouse --
An island retreat open to the future --
Fortified against wind but open to view --
New house, venerable design --
A palette of design elements shapes a lively house --
A delicate balance --
All about the roof --
A big house thinks small --
Rural shapes, uptown details --
A well-crafted cottage --
Weaving house into landscape --
A craftsman bunglaow pays homage to its forebears --
Earth, sky, and water --
A childhood home reborn --
Summer camp, all year long --
Tiny cottages with a generous outlook --
John Connell --
Duo Dickinson --
Jeremiah Eck --
Architects and designers.
ARC
Department of Architecture
Keywords: Architect-designed houses -- United States; Architecture -- United States -- History -- 20th century; Architecture -- United States -- History -- 21st century; Architecture